Sosialisasi Penerapan Video Interaktif pada Materi Proses Transpor dan Pertukaran Zat pada Manusia untuk Meningkatkan Kemampuan Kognitif Siswa Kelas XI di SMA Negeri 3 Langsa - Hartono, Adi; Abdi, Egy (LOSARI DIGITAL, 2025)
The community service activity is motivated by the low utilization of interactive technology in Biology education in schools, particularly in the topic of the processes of transport and exchange of substances in humans. The main focus of this activity is to enhance students' cognitive abilities through the implementation of interactive videos in Biology instruction. The aim of this service is to promote the use of interactive video media to teachers and 11th grade students at State High School 3 Langsa as an effort to transform learning in the digital era. The activity is carried out with a participatory approach through stages of socialization, demonstration of media usage, and evaluation of student understanding. The results of the activity demonstrate an increase in students' enthusiasm for learning, as well as an improvement in the average cognitive test scores following the use of interactive videos. This activity demonstrates that the integration of educational technology in Biology instruction can enhance the effectiveness of learning and reinforce students' understanding of concepts.